Endolymphatic Hydrops is a Marker of Synaptopathy Following Traumatic Noise Exposure - Badash, Ido; Quiñones, Patricia M.; Oghalai, Kevin J.; Wang, Juemei; Lui, Christopher G.; Macias-Escriva, Frank; Applegate, Brian E.; Oghalai, John S. (Frontiers in Cell and Developmental Biology, 2021)
After acoustic trauma, there can be loss of synaptic connections between inner hair cells and auditory neurons in the cochlea, which may lead to hearing abnormalities including speech-in-noise difficulties, tinnitus, and hyperacusis. We have previously studied mice with blast-induced cochlear synaptopathy and found that they also developed a build-up of endolymph, termed endolymphatic hydrops. In this study, we used optical coherence tomography to measure endolymph volume in live CBA/CaJ mice exposed to various noise intensities. We quantified the number of synaptic ribbons and postsynaptic densities under the inner hair cells 1 week after noise exposure to determine if they correlated with acute changes in endolymph volume measured in the hours after the noise exposure. After 2 h of noise at an intensity of 95 dB SPL or below, both endolymph volume and synaptic counts remained normal. After exposure to 2 h of 100 dB SPL noise, mice developed endolymphatic hydrops and had reduced synaptic counts in the basal and middle regions of the cochlea. Furthermore, round-window application of hypertonic saline reduced the degree of endolymphatic hydrops that developed after 100 dB SPL noise exposure and partially prevented the reduction in synaptic counts in the cochlear base. Taken together, these results indicate that endolymphatic hydrops correlates with noise-induced cochlear synaptopathy, suggesting that these two pathologic findings have a common mechanistic basis.